A flood risk decision making approach for Mediterranean tree crops using GIS; climate change effects and flood-tolerant species. Issue 63 (September 2016) - Kourgialas, Nektarios N.; Karatzas, George P.
Graphical abstract: Highlights: Decision making tool for flood risk mitigation in Mediterranean tree crop areas. Flood risk areas in 120 river basins of Crete. Effects of the climate change scenarios in flood risk fruit tree areas. Suggesting flood tolerance fruit trees species. Abstract: The aim of this study is to estimate flood risk in the Mediterranean island of Crete in Greece, using Geographic Information Systems (GIS). The island of Crete, covering an area of 8265 km 2, is one of the most intensively Mediterranean agricultural areas dominated by fruit tree crops. In this study, the factors that are directly related to the creation of a flood are combined in a GIS environment in order to identify the most prone flooding areas. These factors are: (a) the Flow accumulation (F), (b) the Rainfall intensity (R), (c) the Elevation (E), (d) the Geology (G), (e) the Land use (L), and (f) the Slope (S). The initials of these factors gave the name to the proposed method: "FREGLS". The above factors are presented in the form of grid maps and are used in order to determine the final flood risk map. Subsequently, the flood prone fruit tree areas of Crete can be estimated by applying a methodology based on weighting coefficients. The reliability of the final flood risk map is verified using historical flooded data. Additionally, the impact of global climate change scenarios A2 and B1, on flood risk in Crete is examined. Based on the above, this study highlights the flood prone fruit tree areas in the island of Crete under current and future climate conditions. Also, flood-tolerant fruit trees which appear to be economically important for Greece are recommended, especially for the high flood risk areas of the island. The proposed methodology can be applied as a decision making tool for flood risk mitigation to any river basin where tree crops are cultivated.